Historical Representations in Aristotle’s Political Theory - Mara, Gerald (Araucaria, 2022)
Excepting the first half of Athēnaiōn Politeia, whose authorship remains controversial, there are no works of historical inquiry in the Aristotelian corpus. This contributes to the impression that Aristotle’s political theory abstracts from history. This judgment is reinforced by statements in the Poetics diminishing history and historians in favor of poetry and the poets. I offer a more nuanced interpretation, relying principally on an intertextual reading of the Athēnaiōn Politeia and Book Five of the Politics. Both texts direct the reader’s attention to history, though in dramatically different ways. I argue that Aristotle’s uses of history are essential to his conversational engagements with the narratives that human beings construct in order to make sense of their experiences and to clarify options for choice. Read in a dialogic spirit, these texts underscore the possibilities and hazards of civic agency and preserve the importance of history, as well as poetry, for Aristotle’s political theory.